ANALISIS PREDIKSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN RITEL TAHUN 2018-2020 - Pertiwi, Dian; Putri, Alvianita Gunawan (KEUNIS, 2021)
The retail sector is one of the sectors affected by the covid-19 pandemic. Giant is one of the hypermarkets that has closed several outlets from 2019 to 2021 permanently closed. This is due to suboptimal financial performance and exacerbated by the impact of the covid-19 pandemic. The purpose of this study is to analyze financial distress predictions in the retail sector. This study uses a sample of retail public sector companies that run hypermarket, superstore and minimarket businesses. The research analysis technique used the original Altman Z-Score model, which was developed in 1968. This study indicates generally companies are in the “safe” zone for 2018 and 2019, except for HERO, which is in the “gray” zone. Furthermore, in 2020, several companies are still in the "safe" zone, except MIDI and RALS shifting to the "gray" zone and even HERO shifting to the "distress" zone. The implications of the results of this study provide information for retail companies to pay attention to their financial conditions so that they can determine long-term strategies to have long business sustainability.